Uji Daya Terima dan Kandungan Gizi Brownis Daun Bayam Merah dengan Penambahan Tepung Ubi Jalar Ungu sebagai Makanan Selingan Ibu Hamil - Agnes Rantesalu; Hardianti Hardianti; Adillah Imansari (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Background: The prevalence of Chronic Energy Deficiency (SEZ) of pregnant women nationally is still 16.9%, and anemia reaches 27.7%, so the development of local food-based Supplementary Feeding (PMT) is needed. Brownies with the substitution of red spinach as a source of iron and purple sweet potato flour as an energy source have the potential to be developed as an alternative to PMT. This study aims to determine the acceptability and nutritional content of red spinach brownies with the addition of purple sweet potato flour as an interlude food for pregnant women. Method: Design using the Complete Random Design (RAL) method. The formulation of making brownies consists of three treatments with a comparison between (red spinach pureee and purple sweet potato flour) as follows: F1 (50:50), F2 (60:40), and F3 (40:60). The acceptance test was conducted using a hedonic test of color, aroma, taste, and texture on 30 semi-trained panelists. Analysis of nutritional content includes moisture content (thermogravimetry), ash content (dry ashing), protein (Kjeldahl), fat (Soxhlet), carbohydrates (by difference), and Fe (Atomic Absorption Spectrophotometry). The data were analyzed using the Kruskal-Wallis test. Research Results: The acceptability test showed that there was no significant difference between the formulations. The F3 formulation with a ratio of 40% red spinach pureee and 60% purple sweet potato flour obtained the highest preference value and was determined as the best formulation. The nutritional content of the F3 formulation includes protein 10.447%, fat 8.047%, carbohydrates 1.5579%, Fe 0.0005%, moisture content 20.68%, and ash content 1.4875%. Conclusion: There was no significant effect of each formulation on the acceptability of Brownis Suggestion: It is hoped that the next researcher can improve product formulation and processing processes to maintain and increase iron (Fe) levels in brownies.